Projective synchronization of chaotic systems via backstepping design - Tarai, Anindita; Khan, Mohammad Ali (International Journal of Applied Mathematical Research, 2012)
Chaos synchronization of discrete dynamical systems are investigated. An algorithm is proposed for projective synchronization of chaotic 2D Duffing map and chaotic Tinkerbell map. The control law was derived from the Lyapunov stability theory. The numerical simulation results are presented to verify the effectiveness of the proposed algorithm.